The effect of two warm-up protocols on some biomechanical parameters of the neuromuscular system of middle distance runners - Skof, B.; Strojnik, V. (The Journal of Strength and Conditioning Research, 2007)
The objective of this study was to determine the effect of 2 different warm-up protocols on the neuromuscular system of well-trained middle distance runners. Seven runners performed 2 different warm-up protocols, one of which included slow running, stretching, and bounding and sprinting exercises, while the other consisted of slow running and stretching only. Before and after warm-up, contractile properties of the vastus lateralis and quadriceps femoris were monitored with a single twitch test, maximal torque, and the level of muscle activation during maximal voluntary extension. The 2 types of warm-up protocols showed statistically significant differences in the increase of peak knee extension torque and muscle activation level. After warm-up 1 maximal twitch torque was increased and twitch contraction time (CT) was shortened. Both maximal torque and the level of activation were increased. Parameter changes after warm-up 2 were similar to those after warm-up 1 but not statistically significant. Sprinting and bounding as part of athletes' warm-up improve muscle activation.